KID syndrome. Case report. - Samdani, A.J. (European Journal of Pediatric Dermatology, 2008)
Keratitis-ichthyosis-deafness (KID) syndrome is a rare congenital disorder characterized by the association of skin lesions, hearing loss and vascularizing keratitis. KID syndrome is caused by autosomal dominant mutations in the connexin 26 gene (GJB2). KID syndrome belongs to a group of skin disorders marked by dry, scaly skin known as ichthyoses. The skin on the palms of the hands and soles of the feet and the nails may be affected. This disease usually appears in neonates as generalized erythema, sometimes with diffuse scaling and leathery skin. Typical skin changes gradually develop during infancy and include linear and spiny hyperkeratosis of the flexures, and ichthyosis-like scaling on the limbs.